2012
DOI: 10.1002/cne.23044
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chorda tympani nerve injury on cell survival, axon maintenance, and morphology of the chorda tympani nerve terminal field in the nucleus of the solitary tract

Abstract: Chorda tympani nerve transection (CTX) has been useful to study the relationship between nerve and taste buds in fungiform papillae. This work demonstrated that the morphological integrity of taste buds depends on their innervation. Considerable research focused on the effects of CTX on peripheral gustatory structures, but much less research has focused on the central effects. Here, we explored how CTX affects ganglion cell survival, maintenance of injured peripheral axons, and the chorda tympani nerve termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 108 publications
(172 reference statements)
0
16
1
Order By: Relevance
“…This may explain why the robust microglia response to adult CTX across all rNTS zones, such as noted here, is accompanied by a preservation of the CT terminal fields despite temporary loss of afferent input (Reddaway et al, 2012). Microglia have been associated with peripheral nerve regeneration in other systems (DeFrancesco-Lisowitz et al, 2015) and the protective effect of microglia following adult CTX is implicated by studies which impact microglia function.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…This may explain why the robust microglia response to adult CTX across all rNTS zones, such as noted here, is accompanied by a preservation of the CT terminal fields despite temporary loss of afferent input (Reddaway et al, 2012). Microglia have been associated with peripheral nerve regeneration in other systems (DeFrancesco-Lisowitz et al, 2015) and the protective effect of microglia following adult CTX is implicated by studies which impact microglia function.…”
Section: Discussionmentioning
confidence: 69%
“…Minocycline has been used to inhibit microglial inflammatory response while leaving anti-inflammatory and protective functions intact (Kobayashi et al, 2013). As minocycline has no impact on the microglia response after adult mouse CTX (Bartel and Finger, 2013), this suggests that the microglia responding to adult CTX are already in an anti-inflammatory and protective state, preserving the CT terminal field (Reddaway et al, 2012) and possibly facilitating axonal regeneration and the recovery observed (St. John et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because it has been suggested that BDA transport to the brain becomes impaired after long-term neural injury (Reddaway et al, 2012) the long-lasting tracer DiI (1,1'-Dioctadecyl-3,3,3',3'-Tetramethylindocarbocyanine Perchlorate; D3911, Invitrogen) was applied in another group of animals at the time of CTX at P5 or P50 (n = 6/group). Since there is no long-term loss of CT volume after adult CTX (Reddaway et al, 2012), the rats labeled at P50 served as controls. Animals were anesthetized with Brevital ® (50 mg/kg, i.p.)…”
Section: DIImentioning
confidence: 99%
“…Thus, reinnervation occurs regularly in the normal taste system, even in the absence of nerve injury. This rich plasticity might explain why regeneration in the taste system after nerve injury is so robust (Cheal and Oakley, 1977; Reddaway et al, 2012; Shuler et al, 2004). When taste nerves are sectioned, taste buds are either completely lost or exhibit altered morphology (Fujimoto and Murray, 1970; Guagliardo and Hill, 2007; Oakley et al, 1990).…”
Section: Introductionmentioning
confidence: 99%